Folk music from the Ilokos Region and their educational possibilities - Jacinto, Visitacion 1909- (1961)
The aim of the study is to present some Ilokano folk music, analyzed into their scale, melodic, rhythmic, and interval patterns. It desires to see the possibility of bringing Ilokano folk music into the classroom. Ilokano music have many uses. They can be used for developing personality, teaching character and citizenship, igniting nationalism, teaching music skills and a basis for further musical growth and future studies.
Thesis (M.A. Education)--University of the Philippines, Diliman.
Keywords: Folk music -- Philippines -- Ilokos Region